C57BL/6 mice need MHC class II Aq to develop collagen-induced arthritis dependent on autoreactive T cells. Issue 7 (5th October 2012) - Bäcklund, Johan; Li, Cuiqin; Jansson, Erik; Carlsen, Stefan; Merky, Patrick; Nandakumar, Kutty-Selva; Haag, Sabrina; Ytterberg, Jimmy; Zubarev, Roman A; Holmdahl, Rikard
Abstract : Introduction: Collagen-induced arthritis (CIA) has traditionally been performed in MHC class II A q -expressing mice, whereas most genetically modified mice are on the C57BL/6 background (expressing the b haplotype of the major histocompatibility complex (MHC) class II region). However, C57BL/6 mice develop arthritis after immunisation with chicken-derived collagen type II (CII), but arthritis susceptibility has been variable, and the immune specificity has not been clarified. Objective: To establish a CIA model on the C57BL/6 background with a more predictable and defined immune response to CII. Results: Both chicken and rat CII were arthritogenic in C57BL/6 mice provided they were introduced with high doses of Mycobacterium tuberculosis adjuvant. However, contaminating pepsin was strongly immunogenic and was essential for arthritis development. H-2 b -restricted T cell epitopes on chicken or rat CII could not be identified, but expression of A q on the C57BL/6 background induced T cell response to the CII260–270 epitope, and also prolonged the arthritis to be more chronic. Conclusions: The putative (auto)antigen and its arthritogenic determinants in C57BL/6 mice remains undisclosed, questioning the value of the model for addressing T cell-driven pathological pathways in arthritis. To circumvent this impediment, we recommend MHC class II congenic C57BL/6N.Q mice, expressing A q, with which T cell determinants have been thoroughly characterised.